KARAKTERISTIK KEPEMIMPINAN TRANSFORMASIONAL DI LEMBAGA PENDIDIKAN ISLAM - Samsudin Samsudin IAI Sunan Giri Ponorogo; Suci Midsyahri Azizah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2021)
The characteristics of transformational leadership play a very strategic role in determining the progress and setbacks of an educational institution. Educational institutions need a leader figure to advance, develop and bring the institution they lead to a better direction. Transformational leadership is a modern leadership style that is able to change from vision and mission to action and is done by making a clear vision, motivating staff to be creative, innovative, building a learning culture, and building effective communication. The characteristics of transformational leadership become the basis for how a leader should behave and act on his members. The characteristics of transformational leadership include: Idealized Influence, Inspirational Motivation, Intellectual Stimulation, and Individualized Consideration. It seems that these characteristics are in line with the leadership of the Indonesian education figure, Ki Hajar Dewantoro, known by the motto "Ing ngarso sung tulodo ing madyo mangun karso tut wuri handayani", a leadership slogan applied to various forms of organizations or institutions, especially in educational institutions. Karakteristik kepemimpinan transformasional memegang peranan yang sangat strategis dalam menentukan kemajuan serta kemunduran sebuah lembaga pendidikan. Lembaga pendidikan membutuhkan sosok pemimpin untuk memajukan, mengembangkan serta membawa intitusi yang dipimpinnya menuju ke arah yang lebih baik. Kepemimpinan transformasional salah satu gaya kepemimpinan yang modern yang mampu mengubah dari visi misi menjadi aksi dan dilakukan dengan membuat visi yang jelas, memotivasi staf untuk menjadi kreatif, inovatif, membangun budaya belajar, serta membangun komunikasi yang efektif. Karakteristik-karakteristik kepemimpinan transformasional menjadi pijakan bagaimana seorang pemimpin harus bersikap dan berbuat kepada anggotanya, Adapun karakteristik kepemimpinan transformasional meliputi: Idealized Influence, Inspirational Motivation, Intellectual Stimulation, dan Individualized Consideration. nampaknya karakteristik tersebut sejalan dengan kepemimpinan tokoh pendidikan Indonesia yakni Ki Hajar Dewantoro yang dikenal dengan semboyan “Ing ngarso sung tulodo ing madyo mangun karso tut wuri handayani” sebuah slogan kepemimpinan yang diterapkan pada berbagai bentuk organisasi atau lembaga terutama di lembaga pendidikan.